Central nervous system infections and antimicrobial resistance: an evolving challenge. Issue 3 (June 2021) - Nau, Roland; Sörgel, Fritz; Eiffert, Helmut
Abstract : Purpose of review: Antimicrobial resistance is an increasing threat to patients also in nosocomial central nervous system (CNS) infections. The present review focusses on optimizing intravenous treatment in order to achieve sufficient concentrations of antibiotics in the different compartments of the CNS when the causative pathogens have reduced sensitivity to antibiotics or/and the impairment of the blood–cerebrospinal fluid (CSF) and blood–brain barrier is mild. Recent findings: Experience has been gathered with treatment protocols for several established antibiotics using increased doses or continuous instead of intermittent intravenous therapy. Continuous infusion in general does not increase the average CSF concentrations (or the area under the concentration–time curve in CSF) compared to equal daily doses administered by short-term infusion. In some cases, it is postulated that it can reduce toxicity caused by high peak plasma concentrations. In case reports, new β-lactam/β-lactamase inhibitor combinations were shown to be effective treatments of CNS infections. Summary: Several antibiotics with a low to moderate toxicity (in particular, β-lactam antibiotics, fosfomycin, trimethoprim-sulfamethoxazole, rifampicin, vancomycin) can be administered at increased doses compared to traditional dosing with low or tolerable adverse effects. Intrathecal administration of antibiotics is only indicated, when multiresistant pathogens cannot be eliminated by systemic therapy. Intravenous should always accompany intrathecal treatment.